Confucius lives next door : What living in the East teaches us about living in the West - Reid, T.R. (Vintage Books, 1999)
Journalist T.R. Reid recounts his family's years in Japan, exploring how Confucian values shape social order, education, and community life in East Asia. The book contrasts Eastern communal ethics with Western individualism and considers what lessons modern societies can learn from Confucian traditions.